MgSO4 alleviates hippocampal neuroinflammation and BBB damage to resist CMS-induced depression - Wang, Qiaona; Hu, Yuefeng; Li, Fan; Hu, Liyun; Zhang, Yizhu; Qiao, Yunfa; Tang, Chuanfeng; Wang, Renlei (Frontiers in Nutrition, 2025)
PurposeMagnesium sulfate (MgSO4) possesses the advantages of being readily accessible, cost-effective, and having low toxicity. It has potential applications as a neuroprotective agent. The mechanisms underlying the effects of Mg2+ treatment on depression and its neuroprotective properties remain poorly elucidated.MethodsIn this study, we employed chronic mild unpredictable stress (CMS)-induced mice were orally administered with MgSO4 or pioglitazone. The CMS-induced depressive-like behaviors of mice were monitored. After sacrifice, the levels of Mg2+ and inflammatory cytokines were observed. Blood-brain barrier (BBB) permeability and the M1-to-M2 shift of microglia in mouse hippocampus were detected. The expression of proteins in IKK/NF-κB and NLRP3 inflammasome signal pathway were analyzed.ResultsWe found that CMS induced depressive-like behaviors as well as hypomagnesemia in mice, which were accompanied with hypersecretion of inflammatory cytokines in hippocampus of mice. These animals induced by CMS exhibited hippocampal neuroinflammation characterized by an elevated number of Iba+ microglia with enlarged cell bodies and increased branching structures. In CMS-induced mice, MgSO4 alleviated CMS-induced depressive-like behaviors and hypomagnesemia, reduced the levels of inflammatory cytokines in both serum and hippocampus, decreased the number of Iba+ microglia, modulated microglia polarization and repaired the BBB damage. MgSO4 also significantly facilitates the M1-to-M2 shift in CMS-induced mouse hippocampus and lipopolysaccharide (LPS)-induced BV2 microglia. Mechanically, we found that MgSO4 inhibited microglia activation and BBB damage, possibly by suppressing IKK/NF-κB and NLRP3 inflammasome signaling pathways.ConclusionOur findings showed that MgSO4 supplementation played an active role in the prevention and treatment of depression.